Extreme geomagnetic storms, recent Gleissberg cycles and space era-superintense storms - Gonzalez, W.D.; Echer, E.; Gonzalez, A.L. Clúa de; Tsurutani, B. T.; Lakhina, G. S. (My University, 2011)
Extreme historical and space era geomagnetic storms (Î”H or View the MathML source) are studied in terms of their sunspot and Gleissberg solar cycle distributions. Interplanetary and magnetospheric processes associated with the Carrington storm are summarized and the intense storm of August 4, 1972 is discussed in the context of the possibility of having occurred as an extreme storm instead, if the polarity of the related magnetic cloud would have been opposite. We also discuss about superintense geomagnetic storms (View the MathML source) that occurred in the space era, showing their solar cycle and seasonal distributions and also providing averages for the peak values of their main associated interplanetary parameters. A discussion about the possible occurrence of more Carrington type storms is also addressed.
Keywords: Extreme geomagnetic storms; Geomagnetic activity